Pengaruh Pola Perlakuan Over Protective Orangtua terhadap Kemampuan Interaksi Sosial Siswa Kelas XI di SMAN 9 Kota Jambi - Camelia Tampubolon; Rasimin Rasimin; Siti Amanah (Journal on Education, 2023)
This research is motivated by the phenomenon of students whose social interaction skills are low at school and have not been maximized in social interaction in the school environment. This study aims to reveal the quality of over protective, the quality of social interaction skills and to reveal the effect of over protective on the social interaction skills of XI grade students at SMA N 9 Jambi City. The ability of social interaction is the ability of an individual to have a reciprocal relationship between individuals and individuals, groups with groups, and between individuals and groups. treatment Over protective is excessive protection that will close the opportunity for children to learn from the environment so that he does not know how to respond to environmental conditions wisely because the only one in their mind and heart is themselves. This type of research is quantitative with the survey. The data collection technique is using a questionnaire, to determine the accuracy of the instrument validity and reliability tests are carried out. While the data analysis technique used the formula C formula, normality test, linearity test, and simple regression analysis with the help of the SPSS Statistics 24 application. The sampling technique used purposive sampling with a sample of 86 students. The results showed that the effect of over protective on the social interaction skills of a XI students at SMA N 9 Jambi City was at a percentage of 24.5% or 0.245 with a fairly strong classification. Thus, the higher the over protective, the lower the social interaction ability of class XI students at SMA N 9 Jambi City. Guidance and counseling teachers should pay attention and provide assistance to students who have low interaction skills to be able to grow and improve students social interaction skills.